Reservoir Chlorination of the Local Well-Tank-Faucet Systems is a Rapid and Efficient Tool for Controlling Water-related Diseases: Pathogens' Load-clinical Response Rate Correlation - Alaaddin Salih; Dafalla Alam-Elhuda
Chlorination is a chemical method for water disinfection that has been proved to be highly effective in controlling waterborne diarrheal diseases. Most studies have focused on wells' chlorination or later at household level, whereas there have been relatively few researches evaluating the treatment of reservoirs water. Our study followed a mixed design with a before-and-after comparison. It was conducted in a refugee settlement, Um-Baddah Nevachah, which is located in the western outskirts of Khartoum, Sudan. Baseline total coliform test findings have paired areas of four wells that were labeled as sample or control based on fair coin-tossing. A centrally administered water treatment that contains chlorine was added to intervention wells, whereas the other set was considered as chlorine-free placebo. Data were collected 15 days later from the following four main sources: total coliform count, questionnaire-based experimental data trackers, health center records, and face-to-face interviews. The calculated sample size was 341 with corresponding controls selected by systematic random sampling. We found that both groups' prevalences of waterborne diseases were significantly different before the intervention and they shifted later (p = 0.043 vs. p = 0.496, 95% CI). These findings suggest that reservoir chlorination provides prompt disinfection of well-tank-faucet systems water. Highly credible gastroenteritis is a useful tool to detect cases of gastroenteritis in resources limit settings.